More than ticking boxes: Training Lyme disease education ambassadors to meet outreach and surveillance challenges in Québec, Canada - Forest-Bérard, Karl; Ripoche, Marion; Irace-Cima, Alejandra; Thivierge, Karine; Adam-Poupart, Ariane (PLOS ONE, 2021)
Lyme disease (LD) is an emerging public health threat in Canada, associated with the northward range expansion of the black-legged tick (Ixodes scapularis). To address this, public health authorities have been carrying out surveillance activities and awareness campaigns targeting vulnerable populations such as outdoor workers. Implementing these measures is time-consuming and resource-intensive, prompting the assessment of alternatives. Our goal was to evaluate the feasibility and implementation of a training-of-trainers-inspired approach in raising awareness about LD risk and prevention among workers and general population, as well as to evaluate its potential to contribute to provincial LD surveillance efforts. We trained a group of workers from publicly-accessible outdoor parks of the province of Québec to become “LD education ambassadors”. Ambassadors were trained to raise tick and LD awareness, share information on preventive measures in their respective communities, and lead tick sampling activities using a standardised protocol similar to that used by Public Health authorities. Ambassador-led outreach activities, public reach, sampling activities and collected ticks were documented, as well as ambassadors’ satisfaction with the training using forms and semi-structured interviews. In total, 18 ambassadors from 12 organizations were trained. Between June and September 2019, they led 28 independent outreach activities, reaching over 1 860 individuals (from occupational and general public settings) in seven public health units. Ambassadors led 28 tick samplings, together collecting 11 I. scapularis ticks. This study suggests that an adapted training-of-trainers is a feasible approach to raising tick and LD risk awareness among Québec outdoor workers and public. Trained ambassadors have the potential of reaching a large portion of the population visiting or working in outdoor parks while also providing much-needed outreach regarding risk and prevention. Pushing this concept further to include other types of workers and jurisdictions may contribute to national LD surveillance efforts.